Use of guided surgery for implant rehabilitation: Case report (Research, Society and Development, 2024)
Guided implant surgery refers to the digital planning process, being a resource increasingly used by implant dentists. Using specific software, it is possible to “build” all the anatomical structures of a patient and in this way, you can virtually plan your surgery. Reducing surgical time and increasing predictability of success are the main advantages of this technique. The use of the surgical guide for guided surgeries allows highly precise and reliable surgical maneuvers. Another advantage of the technique is the fact that the entire process takes place in flapless conditions, that is, without opening gingival flaps; As a result, low doses of antibiotics, anti-inflammatories, analgesics and even anesthetics are necessary. The patient's comfort during the procedure is superior to the conventional technique, the reduction in edema, pain and the percentage of failure is due to the minimal invasiveness of the technique, which means that all the tissues involved remain much more intact. In this work, a case of jaw surgery is described, implants were installed in the 36 and 37 region through Guided Surgery using the Implacil System. The guided surgery allowed us to achieve an excellent result in relation to the alveolar nerve, the surgical time was greatly reduced, the injuries usually caused to the gingival tissues were minimal and the 3D positioning of the implants was ideal. We concluded that the technique is efficient and reproducible, and can be used in the implant dentist's daily routine.